Diversifikasi Produk Ikan Asap Cakalang (Katsuwonus pelamis) dengan Penambahan Ekstrak Kulit Manggis Terhadap Mutu Sensorik - Radjawane, Christy; Badaruddin, M. Iksan; Yekwan, Makdalena (Nekton, 2022)
Skipjack fish is a prima donna for Sorong City, West Papua fishing communities. In general, the people of Sorong City process skipjack into smoked fish. The smoking process is carried out using traditional techniques where the smoke source is in direct contact with the raw material, thus significantly affecting the appearance of smoked fish. Using mangosteen rind extract, carried out with a precipitating process before the fish is smoked, will give a more attractive color and appearance. The mangosteen rind extract used can be used as a natural coloring agent to give fish a more attractive color when smoked traditionally. This study aims to determine the effect of mangosteen rind extract on the sensory quality of smoked skipjack and determine the best concentration of mangosteen rind extract on smoked skipjack products. This study uses an experimental method where the research is carried out by giving treatment to the object of research with 3 treatments, 15 panelists, and tested using the Kruskal Wallis test. Statistically, the addition of mangosteen rind extract to smoked skipjack products significantly affected the product's sensory value, and the best sensory test of smoked skipjack products with the addition of mangosteen rind extract was in treatment A2 and the lowest was in treatment A0.